Electrodialytic separation of levulinic acid catalytically synthesized from woody biomass for use in microbial conversion. (10th January 2017) - Habe, Hiroshi; Kondo, Susumu; Sato, Yuya; Hori, Tomoyuki; Kanno, Manabu; Kimura, Nobutada; Koike, Hideaki; Kirimura, Kohtaro
Abstract : Levulinic acid (LA) is produced by the catalytic conversion of a variety of woody biomass. To investigate the potential use of desalting electrodialysis (ED) for LA purification, electrodialytic separation of levulinate from both reagent and cedar‐derived LA solution (40–160 g L −1 ) was demonstrated. When using reagent LA solution with pH5.0–6.0, the recovery rates of levulinate ranged from 68 to 99%, and the energy consumption for recovery of 1 kg of levulinate ranged from 0.18 to 0.27 kWh kg −1 . With cedar‐derived LA solution (pH6.0), good agreement in levulinate recovery (88–99%), and energy consumption (0.18–0.22 kWh kg −1 ) were observed in comparison to the reagent LA solutions, although a longer operation time was required due to some impurities. The application of desalting ED was favorable for promoting microbial utilization of cedar‐derived LA. From 0.5 mol L −1 of the ED‐concentrated sodium levulinate solution, 95.6% of levulinate was recovered as LA calcium salt dihydrate by crystallization. This is the first report on ED application for LA recovery using more than 20 g L −1 LA solutions (40–160 g L −1 ). © 2017 American Institute of Chemical Engineers Biotechnol. Prog., 33:448–453, 2017